Analysis of Competency Gap in the Civil Servants of Southwest Papua Province and CompetencyDevelopment Strategies - Rengen, Dewiyanti; Hasniati, ‎; Ibrahim, Akmal; Purna, Zarni Adia (KnE Social Sciences, 2025)
This study analyzes the competency gap of civil servants (ASN) in Southwest Papua using a thematic analysis approach to qualitative data. It studies interviews from 20 informants consisting of 13 indigenous Papuans and 7 non-indigenous Papuans, selected through purposive sampling. Data were collected through in-depth interviews, focus group discussions, and document analysis. Data processing was conducted using NVivo software through systematic stages of open coding, axial coding, and theme development. The research findings identified three primary themes explaining the competency gap phenomenon: structural incongruence, adaptive capacity disparities, and professional identity dualism. Findings reveal that the competency gap among civil servants in Southwest Papua is multidimensional and requires a comprehensive approach considering the unique geographical, socio-cultural, and institutional contexts. The study proposes the concept of “adaptive contextualization” as an integrated framework for civil servant competency development in Southwest Papua, encompassing three key elements: structural flexibility, adaptive capacity enhancement, and identity integration. Recommended competency development strategies include decentralization of development programs, adaptive learning approaches, incorporation of local wisdom into competency standards, and evidence-based implementation. This study contributes to understanding the competency gap attributes of civil servants in regions with unique geographical and socio-cultural characteristics and provides a concept for developing effective strategies.